Dextrocardia with Situs Inversus Totalis and Subaortic-Type Double Outlet Right Ventricle in an Adult: A Case Report - Dian Komala Dewi; Zakir Fendy Abdul Razak (The International Journal of Medical Science and Health Research, 2026)
Background: Dextrocardia with situs inversus totalis (SIT) is a rare congenital condition, and significant congenital heart disease (CHD) complicates only approximately 0% to 10% of affected individuals. The coexistence of subaortic-type double outlet right ventricle (DORV) in adults is exceptionally uncommon. Mirror-image anatomy further complicates cardiovascular assessment and may lead to diagnostic misinterpretation without systematic segmental analysis and multimodal imaging. Case Presentation: A 29-year-old man presented with chronic cyanosis, exertional dyspnea, and a three-month history of worsening symptoms accompanied by 5 kg of unintentional weight loss. Chest radiography demonstrated a right-sided gastric bubble. Transthoracic echocardiography identified a large subaortic ventricular septal defect (VSD) measuring 27.3 mm and a left ventricular ejection fraction of 51%. Contrast-enhanced cardiac computed tomography (CT) with three-dimensional reconstruction confirmed dextrocardia, SIT, atrial situs inversus, a right aortic arch, subaortic-type DORV with aortic override, and imaging features suggestive of pulmonary hypertension. Conclusion: This case underscores the diagnostic value of cardiac CT in definitively classifying complex conotruncal anatomy in the setting of mirror-image laterality. Early referral to an adult congenital heart disease center and formal pulmonary vascular assessment are essential when corrective intervention remains under consideration. Radiologists should maintain high suspicion for visceral situs inversus when a right-sided gastric bubble is identified on chest radiography.